Autumn festivals - Rosen, Mike (Wayland Hove, 1990)
Autumn Festivals by Mike Rosen is an insightful exploration of seasonal celebrations and traditions that take place during the autumn months. The book provides an engaging look at how different cultures around the world celebrate harvest time, the changing of the seasons, and various festivals linked to this time of year. Through vibrant illustrations and captivating text, Rosen highlights the significance of these festivals, offering readers an understanding of their cultural, historical, and social importance. It$1 (Bs an excellent resource for young readers, teachers, and those interested in learning about global customs.s